An integrated project management control system - Yuh, Cherng; Pichai Nimityongskul; Ping Kunawatsatit; Carmichael, D.G.; Republic of China (RSEA) (Bangkok : Asian Institute of Technology, 1985)
In this study, the construction management tasks of project planning, scheduling, and controlling are discussed. A BASIC Micro-Computer program group for project schedule and control is also developed. Attention is concentrated on the project control system, based upon the Critical Path Method (activity of arrow) as the research topic. Data and relevant information of a building construction project were collected. The proposed integrated project management program is tested, and proves to be a very useful method for project management.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Electronic data processing -- Construction industry; Construction industry -- Management